1993
DOI: 10.1038/bjc.1993.128
|View full text |Cite
|
Sign up to set email alerts
|

Gallium-67 radiotoxicity in human U937 lymphoma cells

Abstract: Summary Promising clinical results have been obtained with radiolabeled antibodies in lymphoma patients. The higher uptake by lymphomas of 67Gallium (6'Ga) compared with monoclonal antibodies makes selective radiotherapy by the widely available 67Ga appealing. However, the gamma radiation of 67Ga uised in scintigraphy is considered to be almost non-toxic to lymphoma cells. However, in addition to photon radiation 67Ga emits low energy Auger electrons and 80-90 keV conversion electrons which could be cytotoxic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The radiation energy of these electrons is deposited within the direct vicinity of the disintegrating radionuclide. This category includes gallium-67 and indium-111 [23][24][25][26]. The question arises as to whether such a radionuclide, coupled to a peptide, is sufficiently internalized by the cell that the emitted low-energy particles will reach the nucleus.…”
Section: Choise Of a Suitable Radionuclidementioning
confidence: 99%
“…The radiation energy of these electrons is deposited within the direct vicinity of the disintegrating radionuclide. This category includes gallium-67 and indium-111 [23][24][25][26]. The question arises as to whether such a radionuclide, coupled to a peptide, is sufficiently internalized by the cell that the emitted low-energy particles will reach the nucleus.…”
Section: Choise Of a Suitable Radionuclidementioning
confidence: 99%
“…Gallium as radiometal is of even broader interest in nuclear medicine because it is also available as 67 Ga (t 1 ⁄2 78 hr), which is not only a ␥-emitter useful for tumor diagnosis (␥-camera scintigraphy, SPECT) but also an emitter of Auger (0.1-8 keV) and conversion (80 -90 keV) electrons, which makes it attractive for internal radiotherapy. 23 The radiotoxicity of 67 Ga has been demonstrated in vitro in a lymphoma cell line 24 and myeloid leukemic blasts. 25 The use of a low-energy emitter might increase the therapeutic index because most of the electrons deposit their energy within the target, i.e., the tumor, thereby minimizing collateral damage.…”
mentioning
confidence: 99%
“…This may reduce the need for the radionuclide to be localized in specific subcellular compartments in order to be effective. 67 Ga has been explored previously, to a limited extent, as a radionuclide for therapeutic applications [9][10][11][12][13]. In vitro results were promising and showed that treatment with 67 Ga diminished clonogenic capacity in human U937 lymphoma cells [9] and in myeloid leukemic blasts from acute myeloid leukemia patients [10].…”
Section: Introductionmentioning
confidence: 81%